Antimicrobial usage assessment and the factors associated among small-scale household dairy farms in a district of southern India. - Prabhu, Shwetha; Das, Rinila; Kharate, Arun; Nayak, Ajith M; Vyas, Navya (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The study was primarily conducted to assess antimicrobial usage, associated factors, and animal health management practices in small-scale household dairy farms in a district of southern India. Materials and Methods: A total of 330 dairy farmers participated in the study, and single-stage cluster sampling was performed, followed by probability proportional to size sampling. A semi-structured, validated questionnaire and a checklist were used to collect the data. Results: Only a few dairy farmers knew about antimicrobials (33%) and antimicrobial resistance (AMR) (10.9%). All 330 dairy farmers were using antimicrobials. The factors that influenced dairy farmers’ decisions to use antimicrobials for their cattle were veterinarian advice (100%), para-veterinarian advice (96.3%), peer influence (31.2%), and previous experience of using antimicrobials (12.4%). None of them were aware of the drug withdrawal period and followed it. Significant differences in completing the full course of antimicrobial treatment as prescribed have been observed with increasing levels of education (p < 0.001). Conclusion: Despite the wide usage of antimicrobials in dairy farms, there was a significant lack of knowledge among dairy farmers regarding antimicrobials and AMR. The study emphasizes the need for targeted educational interventions to improve farmers’ understanding of antimicrobial use and resistance, promote responsible practices, and enhance animal health management. J. Adv. Vet. Anim. Res., 12(2): 445–453, June 2025 http://doi.org/10.5455/javar.2025.l911